Analisis Kualitas Website Portal Berita Dan Opini Mojok.Co Menggunakan Webqual 4.0 Dan Importance-Performance Analysis - Muhammad Jordan Farrell; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
News and opinion portal website Mojok.co continues to experience a downgrade in its quality that cost many loss like a decrease in total visitor of the website and still lost to the other competitor in news and opinion portal . Other than quality issues Mojok.co also want to create a strong engagement with the reader and through fullfilling a good customer satisfaction. So this research focussing on two main things which is measure website quality of Mojok.co and anlyze if a website quality have an significant impact on customer satisfaction. To measure website quality then it is used WebQual 4.0 then the results will be map on Importance-Performance Analysis. This research use 3 independent variable which is usability, information quality and service interaction quality. There is also one dependent variabel customer satisfaction. The result of the measurement using 100 responden show that 6 attribute statement included in IPA first kuadran and 4 attribute statement included in IPA third kuadran. Regresson analysis conducted a constant for each WebQual dimension in the amount of 0, 233; 0,136; and 0,068 for each dimension usability, information quality and service interaction quality. The T Test conducted that usability and information quality dimension influence customer satisfaction partially, and F Test conducted that all dimensions in WebQual influence customer satisfaction by together. From the result of the influence analysis can be concluded that the improvement must be prioritized based on gap analysis and its dimension in order usability, information quality, and service interaction quality.